How to survive in school using library resources and reference materials. (Mount Kisko, N.Y. The Center for Humanities, 1978)
Surveys the basic library resources, instructs students in the use of card catalog and reference collection and provides guidelines for the efficient organization of research.
Keywords: Libraries and readers; Library resources